Improving the Efficiency of Ocean Freight Orwarding Procedure for Import Cargo Via full Container Load Shipping at Anh Phu Logistics Company Limited - Phan, Thi My Hoa (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Logistics and Digital Supply Chain Management; 2021-2025.